ANALISIS FAKTOR MEDIASI PENGARUH BRAND EXPERIENCE TERHADAP BRAND LOYALTY PADA SAMSUNG - AFIFAH SALMA; KLEMENS WEDANAJI PRASASTYO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
The purpose of this study was to analyze and determine the mediating factors of Brand Passion (BP),Self-Brand Connection (SBC), Brand Affection (BA), and Brand Trust (BT) on the effect of Brand Experience (BE) on Brand Loyalty (BL) on Samsung in Bekasi City. The objects used in this study are Samsung consumers as well as active Samsung users in Bekasi City. The method used to select samples in this study was purposive sampling 372 respondent data were taken which were Samsung consumers as well as active Samsung users in Bekasi City. Structural Equation Modeling Partial Least Square 4.0 and IBM SPSS25 were used to test the data obtained. The result of this study are BE has an influence on BL. BP, SBC, BA, and BT variables partially mediate the effect of BE on BL for Samsung consumers in Bekasi City